- Effectiveness of Education on Increasing Knowledge, Attitude, and Practice of Hygiene Behavior and Health Attitudes of Preschool-Aged Teachers in North Sumatera. Indonesia: Hygiene Behavior and Health Attitudes of Preschool-Aged Teachers - Rina Amelia (Journal of Saintech Transfer, 2019)
Hygiene Behavior and Health Attitudes (HBHA) in schools is a set of behaviors practiced by students, teachers, and the school community based on awareness as a learning outcome so that they can independently prevent disease, improve their health, and play an active role in creating a healthy environment. The purpose of this study was to analyze the effectiveness of providing education to the level of knowledge, attitudes, and practice of preschool-aged teachers of HBHA in Amanah Preschool-Aged, Langkat Regency, North Sumatera. The research design is a quasi-experimental method with one sample pretest-post design. The population in this study were all Amanah Preschool-Aged teachers in Langkat Regency, North Sumatra. The source of research data is primary data, and data collection is done by interview and observation. Data processing was using SPSS and data analysis using Dependent T-Test. The level of knowledge is the good level with scores before and after the provision of education 80% and 86.7%. The level of attitude category is good, with all the respondents about 15 people (100%), the total score before and after giving the same 100%. The level of practice category is good with scores before and after providing the education 66.7% and 93.3%. The Analysis using dependent T-Test concluded that there is a difference the level of knowledge and practice of HBBA, while for attitudes, no differences found.